A produção científica sobre didática na região centro-oeste: um estado da arte a partir de três programas de pós-graduação (2004-2010) - Rodrigues, Adriana (2015)
This doctoral research is linked to the line of Knowledge Research and Educational Practices, the Master\'s and Doctorate Programs in Education at the University of Uberlândia - UFU. Considering the needs presented in the Brazilian educational context, with regard to learning disabilities and scientific production of didactic, as the area responsible for the theoretical basis of educational practices at school, this research was first purpose, seizure of that scientific production. Was elected as an object of study that produced didactic knowledge, embodied in Articles prepared by teachers of the lines of research, the Graduate Program in Education located in the Midwest Region, from 2004 to 2010. This research is justified considering the contributions that a body of knowledge, inferred of the subject matter, can bring to think the educational practice, the constitution of teaching with regard to their investigative field, signal trends, objects being neglected and theoretical foundations that support these productions, which are important to the overall understanding of didactic knowledge produced in the academy and how it can support interventions in school practices. It aimed to unveil the conceptions and the knowledge produced on Teaching in Brazilian graduate, to what extent these views allow or not the teaching-learning relationship that promotes development. The specific guiding objectives were outlined to map scientific production of teaching, understand the constitution of this in teaching and research, analyze and discuss the theoretical and methodological aspects that sustain the knowledge produced, as well as highlight the contributions of the teaching thinking is guided Theory of Developmental Education. To this end, there was a state of the art using as theoretical foundation, the historical materialist method dialectical and theoretical and operational principles of developmental teaching. It was found as the most significant trends that scientific didactics production has prioritized as an object of study, training and professionalization of teachers for performance in higher education, focusing more on the teaching-learning area, the size of the grounds, to the detriment modes and conditions in which teaching is performed. The results indicate the need for education organization intends to provide the student\'s development in the context of the classroom taking into account the formation of theoretical thinking and social and cultural practices, which are embedded in the school routine. Evaluation as a teaching resource that contributes to the quality of teacher education, taking into account that, beyond the realm of academic content, you need to consider creativity, affection, subjectivity, emotional and motivations. How overlooked aspects were identified little expression studies with an interest in early childhood education, primary and secondary education, with total absence of studies on adult education, as well as the relationships that are established in the school\'s organizational structure, materials textbooks used in the special needs presented by students. With regard to the privileged location are few studies that direct their attention to the classroom, to the organization\'s context of school or various locations.